Supervisors’ Written Feedback and Students’ Responses Towards Feedback on Undergraduate Research Proposals - Aridah, Aridah; Hambali, Muhamad; Ping, Maria Teodora; Setiawan, Iwan; Limbong, Effendi (IJEE (Indonesian Journal of English Education), 2024)
This study explores the types of feedback given by supervisors on undergraduate thesis proposals and investigates how the students respond to the feedback. The data were collected from research proposal pages containing feedback and interview transcripts through a mixed method with a case study design. Four supervised students of the English Department at one university in Samarinda, whose graduation was delayed due to incompletion of their theses, participated in this study. The quantitative data covered the total feedback occurrences and were analyzed using frequency and percentage. The qualitative data were taken from the interview transcript and were analyzed using a coding scheme based on feedback typologies by Ellis (2009), Cárcamo (2020), and Pearson (2022). The findings revealed that from a number of feedback types expected in this study, only 8 were identified, with implicit feedback being the most common. The students perceived supervisors' feedback as helpful and useful for revising their proposals, but they preferred explicit feedback because of its direct error corrections. Some supervisors' comments were unclear, making it difficult for the students to understand and do revisions. Yet, they hesitated to communicate with their supervisors because they were afraid and concerned about politeness. The study highlights the importance of aligning supervisor feedback practices with students' expectations and emphasizes the need for effective communication and good relationships to prevent delays in thesis completion.